Icarus: An Android-Based Unmanned Aerial Vehicle (UAV) Search and Rescue Eye in the Sky - Delos Santos, Manuel Luis Concha; Dasalla, Jerum B.; Feliciano, Jomar C.; Cabatay, Dustin Red B. (International Journal of Computing Sciences Research, 2023)
Purpose – The purpose of this paper is to develop an unmanned aerial vehicle (UAV) using a quadcopter with the capability of video surveillance, map coordinates, a deployable parachute with a medicine kit or a food pack as a payload, a collision warning system, remotely controlled, integrated with an android application to assist in search and rescue operations. Method – Applied research for the development of the functional prototype, quantitative and descriptive statistics to summarize data by describing the relationship between variables in a sample or population (Kaur et al., 2018). The quadcopter underwent an evaluation using a survey instrument to test its acceptability using predefined variables to select respondents within Caloocan City and Quezon City, Philippines.   Results – Demographic profiles and known issues and concerns were answered by 30 respondents. The results were summarized and distributed in Tables 1 and 2. Discussion - In terms of demographic profiles, the number of SAR operators within the specified areas is distributed equally, most are male, single, and within the age bracket of 31 and above. In issues and concerns, the most common type of search and rescue was ground search and rescue. Human error is the primary cause of most injuries in operating units. The prototype was useful and everyone agreed, in terms of acceptability, drone technology will improve search and rescue operations. Conclusion – The innovative way of utilizing Android and drone technology is a new step towards the improvement of SAR operations in the Philippines. Recommendations – The LiPo battery must be replaced with a higher capacity and the drone operator should undergo a training course and secure a permit from the Civil Aviation Authority of the Philippines (CAAP). Social Implication - Some people are scared of drones due to privacy issues and fears that they could be used to spy against them.